Penyuluhan Sunat Massal Ceria : Langkah Sehat Menuju Masa Depan di Kampus Universitas Sunan Giri Surabaya - Salwa Sabrina; Maulidia Ilham Fadilah; Nurul Arifin; Wakid Evendi; Terubus Terubus; Pratolo Saktiawan; Didit Darmawan; Muhammad Zakki; Adi Herisasono; Rommy Hardyansah; Muchamad Catur Rizky (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
The implementation of promoting circumcision practices, the method used in the activity is the ABCD (Asset Based Community Development) method. This ABCD method emphasizes community assets and strengths compared to their needs or problems. The mass circumcision counseling program "Ceria: Healthy Steps Towards the Future" at the Sunan Giri University Surabaya (Unsuri) campus seeks to increase students' knowledge about the importance of reproductive health. In addition to discussing circumcision practices, this activity also teaches participants about the importance of circumcision from a religious perspective and health benefits. Although this program has had many beneficial impacts, some groups still have difficulty understanding and participating, and they continue to have concerns about its safety and effectiveness. As a result, this counseling is a valuable forum to discuss health issues, foster community cohesion, and raise awareness of the importance of reproductive health prevention. The success of this program is expected to be a stepping stone for broader health programs in the future and inspire children to actively participate in preserving their environment and health.